2021
DOI: 10.3389/fped.2021.668978
|View full text |Cite
|
Sign up to set email alerts
|

Early Serum Infliximab Levels in Pediatric Ulcerative Colitis

Abstract: Background: Data on serum infliximab concentrations during induction in pediatric ulcerative colitis are limited. The study aim is to evaluate the relationship between serum infliximab concentrations during induction and short-term clinical remission in children with ulcerative colitis.Methods: We carried out a prospective, multi-center cohort study in pediatric patients with ulcerative colitis. Serum infliximab concentrations were collected at peak dose #1, week 1, trough pre-dose #2, and trough pre-dose #3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…It was previously demonstrated that a high proportion of anti-TNFα treated children with IBD will eventually undergo treatment escalation either by increasing dose or by decreasing the interval between infusions/injections (2,16). Furthermore, a clear association between higher TC and both clinical and mucosal response has been established for adalimumab and infliximab (3)(4)(5). In adalimumab treated patients, as was shown in previous studies (17,18), we found that interval change resulted in an almost linear response in adalimumab TC, whereas in infliximabtreated patients, the response to interval change was less predictable and the response to dose escalation could not have been predicted at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously demonstrated that a high proportion of anti-TNFα treated children with IBD will eventually undergo treatment escalation either by increasing dose or by decreasing the interval between infusions/injections (2,16). Furthermore, a clear association between higher TC and both clinical and mucosal response has been established for adalimumab and infliximab (3)(4)(5). In adalimumab treated patients, as was shown in previous studies (17,18), we found that interval change resulted in an almost linear response in adalimumab TC, whereas in infliximabtreated patients, the response to interval change was less predictable and the response to dose escalation could not have been predicted at all.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of weight on the clearance of mAbs is not linear (20,29). A nonlinear correlation between body weight and infliximab clearance have been seen in several pediatric studies (5,16,29,30). In contrast to infliximab, adalimumab dose is constant and is not determined based on body weight, thus, the effect of age, body weight, and body surface area (BSA) on TC response could be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 However, approximately 20%-30% of UC patients experience poor treatment response to IFX and disease progression, which further impairs their long-term clinical outcomes. 9,10 Hence, it is obligatory to identify potential biomarkers to monitor disease progression and predict IFX efficacy in UC patients.…”
Section: Introductionmentioning
confidence: 99%
“…IFX, as one approved biologic regimen for UC management, shows a superior short‐term clinical response rate and long‐term mucosal‐healing rate in treating moderate‐to‐severe UC patients 4,7,8 . However, approximately 20%–30% of UC patients experience poor treatment response to IFX and disease progression, which further impairs their long‐term clinical outcomes 9,10 . Hence, it is obligatory to identify potential biomarkers to monitor disease progression and predict IFX efficacy in UC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors may affect trough concentrations of these medications, including disease subtype, extent, phenotype, degree of inflammation, serum albumin, concomitant immunomodulator, patient's sex, and body mass index. [ 5 6 7 ] In clinical care, TDM can be performed proactively or reactively. In reactive TDM, serum drug level and presence of ADA are measured in patients receiving a biological agent, in response to evidence of active disease or incomplete response to the biologic that is confirmed with objective evidence via endoscopy, biochemically, or radiographically.…”
Section: Introductionmentioning
confidence: 99%